Sorption Efficiency of Bentonite in Removal Cd from Aqueous Solutions - Muhammad Awadh, Salih; Esmaeel Al-Jubury, Harith (Iraqi Journal of Science, 2023)
A series of adsorption laboratory experiments were conducted to study the sorption efficiency of bentonite in removal Cd from aqueous solutions. The bentonite was found to be a good receptive to the adsorption of Cd under specific laboratory conditions. The sorption capacity for Cd onto bentonite was investigated through the variation in pH and initial Cd2+ concentration. The sorption efficiency onto bentonite was examined as a function of pH, initial ion concentration, equilibrium reaction time and solid mass/ liquid volume ratio. The maximum sorption (%) of Cd from solutions were determined when solid to liquid ratio is 2 gm of bentonite versus 50 ml solution, the equilibrium reaction time is 50 minute at pH ranges from 5-7. The sorption was gradually increased with increasing concentrations of Cd in solution, it was found that the highest sorption was 81.7% when the Cd concentration in the solution was 80 ppm, but it suddenly declined to 72% with highest concentrations (100 ppm Cd) because of competing cations on the negative sites on the surface of clay minerals.